Anthropocentric Analysis of Emotional Communication in English and Uzbek: A Cross-Cultural Perspective - Sabirova Shirinoy Maksudovna (International Scientific and Current Research Conferences, 2026)
Language is more than a means of communication; it reflects how people perceive the world, interact with others, and express their emotions. From an anthropocentric perspective, language is closely connected with human cognition, culture, and social behavior. This study examines emotional communication in English and Uzbek by comparing the linguistic means used to express feelings, attitudes, and interpersonal relationships. The research focuses on emotional vocabulary, phraseological expressions, metaphors, and culturally specific communicative patterns. A qualitative comparative method was employed using examples from authentic speech, literary texts, dictionaries and linguistic studies. The findings demonstrate that although basic human emotions are universal, their linguistic realization differs according to cultural values and communicative traditions. English communication generally emphasizes emotional restraint, individual responsibility and politeness, while Uzbek communication reflects sincerity, collectivism, respect for elders, and social solidarity. The study contributes to anthropocentric linguistics, cognitive linguistics, pragmatics and intercultural communication by illustrating how emotional language embodies cultural identity and human experience.